Recognition of c. 1780 Ma magmatism and metamorphism in the buried northeastern Gawler Craton: Correlations with events of the Aileron Province - Reid, A.; Jagodzinski, E.; Wade, C.; Payne, J.; Jourdan, Fred (Elsevier BV, 2017)
The far northeastern Gawler Craton, South Australia, lies at the northern margin of one of the major building blocks of the Australian continent and is a region that is important in models for the Proterozoic tectonic evolution of Australia. However, this region is overlain by Phanerozoic sedimentary cover and consequently has had no previous geological study. We report the lithotypes, geochronology, geochemistry and isotopic composition of rocks recovered in a mineral exploration drill hole in the far northeastern Gawler Craton, the sole drill hole to sample crystalline basement in this region. Lithologies within the drill hole are garnet- and pyrite-bearing metasedimentary gneiss, pyroxenite and gabbroic intrusions, along with granitic bodies. Metasedimentary gneiss has a maximum depositional age of 1841 ± 4 Ma and a provenance pattern more similar to rocks of the Aileron Province of the Arunta Region, central Australia, in particular the Lander Rock Formation, than to other metasedimentary rocks of the Gawler Craton. Amphibolite facies metamorphism occurred at c. 1780 Ma and was synchronous with emplacement of high Mg, crustally contaminated mafic rocks, along with several types of felsic intrusion. This metamorphic event is very similar in age and style to the Yambah Event of the Aileron Province, and has not been documented previously in the Gawler Craton. The overall geological features of this portion of the northern Gawler Craton support models that link it with the Aileron Province of the Arunta Region. The rocks of drill hole TB02 underwent thermal resetting recorded by a biotite 40Ar/39Ar age of c. 480 Ma, likely as a result of the Cambro-Ordovician Delamerian Orogeny along the eastern margin of Gondwana.